Meningkatkan Ketrampilan Mengajar Melalui Pengembangan Pembelajaran Microteaching Berbasis Experiential Learning Melalui Peran Model Dan Kelompok - Supiyanto, Yudi; Sulistyaningrum, Heny (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2019)
AbstractThis study aims to develop Microteaching learning models based on experiential learning through the role of models and groups (practicality, efectiveness).The design of this research is development research and to carry out this research development methods will be used from Plomp which consists of five stages, namely: (1) the initial assessment stage, (2) the design stage, (3) the realization / construction stage, (4) the test, evaluation and revision stages, and (5) the implementation phase. Furthermore, to assess the quality of the Microteaching learning model based on Experiential Learning, Nieveen's criteria are used to fulfill practice, and effectiveness. The results of the study based on aspects of practicality namely management, lecturer and student activities towards learning using microteaching learning models based on experiential learning through the role of models and groups. with an overall average of 3.5 with very good indicators, the practicality criteria are very practical. Then the results of the above effectiveness data from the tabulation of student learning outcomes, lecturer response questionnaires, and student response questionnaires to learning using microteaching learning models based on experiential learning through the role of models and groups. with a good average learning outcome. The implications of this study will be able to improve the skills of final-level students when they implement a field experienceÂ  program at school.